Strategi Pemanfaatan Media Audio Visual untuk Peningkatan Hasil Belajar Bahasa Inggris - Asep Saefurahman; Visca Ayu Solikhah (Jurnal Riset dan Inovasi Manajemen, 2025)
In the world of education, students' English language skills cannot be separated from the learning process provided by lecturers. Lecturers as facilitators try to provide the best teaching and learning process for their students. English is a course that develops communication skills both orally and in writing, understanding and expressing information. This course is no longer just a course that is limited to grammar, but can also develop students' skills in communicating English orally and in writing. For this reason, a creative approach is needed that can make students more active and interesting in learning English. One of the approaches provided by lecturers is learning English by utilizing audio-visual media, namely using videos, films, and music. In teaching English material, the use of this learning media is one of the right learning media to use. The purpose of this journal is to provide strategies in utilizing audio-visual media to improve students' English learning outcomes. Technically, the strategy for utilizing audio-visual media in the process of teaching and learning English is divided into three stages, namely preparation, use and the last is follow-up after use. This media utilization strategy will make English learning more effective, interactive and interesting. Lecturers will be more optimal in delivering materials and students will find it easier to understand.